School mathematics and studies at university - Apynis, Antanas; Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2005)
The article analyzes mathematics programmes at schools of general education. It also discuss wheather they are sufficient to prepare for one’s studies at university. The conclusion is drawn that teaching mathematics at secondary schools should be revised.